MERAKIT KETAPANG: MENANAM HARAPAN DI PEDALAMAN KATINGAN MELALUI KETAHANAN PANGAN - Fahdiani, Dina (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The background to this research problem is the condition of SMAN 1 Katingan Hulu, located in a remote area with limited access, where the community is predominantly gold mining workers. This results in underdeveloped farming skills, resulting in a heavy reliance on urban vegetable supplies. However, this situation is seen as an opportunity to introduce contextual learning about food security through the innovative